PERLINDUNGAN HUKUM KONSUMEN ATAS PEREDARAN KOSMETIKA ILEGAL (STUDI TERHADAP PUTUSAN NOMOR 873/PID.SUS/2019/PN BPP) - Frizka Ariana Putri; A. M. Tri Anggraini (Jurnal Hukum Adigama, 2021)
In Law No.8 of 1999 concerning Consumer Protection Article 4 paragraph (3) states that consumers have the right to obtain correct, clear, and honest information regarding the conditions and guarantees of goods and / or services,This study aims to determine the form of supervision and legal protection for consumers against products according to the UUPK against illegal cosmetics that do not have a distribution permit circulating online and the efforts of the Food and Drug Supervisory Agency in supervising the circulation of illegal cosmetics in circulation. product. As in the Regulation of the Head of the Drug and Food Supervisory Agency Number 19 of 2015 concerning Technical Requirements for Cosmetics articles 5,6, and 7 which contain clear and correct label markings or information on a product in the package. This research is normative legal research. The research data was obtained by interviewing dermatologists & beauticians, YLKI, BPOM and literature study. The type of research used by the writer is normative. To support this research, the author uses the type of literature study research, which examines several documents related to research. The method used is a normative research method using a statutory approach (statue approach) and a case approach (case approach). Analysis in accordance with the provisions of Law Number 8 of 1999 concerning Consumer Protection and BPOM Regulation Number 30 of 2017 concerning Supervision of Importation of Drugs and Food into Indonesian Territory.